2013
DOI: 10.1371/journal.pone.0063706
|View full text |Cite
|
Sign up to set email alerts
|

Primary Treatment Results of Nasopharyngeal Carcinoma (NPC) in Yogyakarta, Indonesia

Abstract: IntroductionNasopharyngeal Carcinoma (NPC) is a major health problem in southern and eastern Asia. In Indonesia NPC is the most frequent cancer in the head and neck area. NPC is very sensitive to radiotherapy resulting in 3-year disease-free and overall survival of approximately 70% and 80%, respectively. Here we present routine treatment results in a prospective study on NPC in a top referral; university hospital in Indonesia.MethodsAll NPC patients presenting from September 2008 till January 2011 at the ear,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
1
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 37 publications
3
34
1
5
Order By: Relevance
“…The prevalence of nasopharynx cancer in developing countries is higher, and this is attributed to the higher exposure of inhabitants to a variety of risk factors and lower budget allocations for health. For these people, diagnosis is often made when the disease is already in advanced stages, and, with the lack of access to treatment, the metastasis of nasopharynx cancer can be observed more often in these areas 36, 37.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of nasopharynx cancer in developing countries is higher, and this is attributed to the higher exposure of inhabitants to a variety of risk factors and lower budget allocations for health. For these people, diagnosis is often made when the disease is already in advanced stages, and, with the lack of access to treatment, the metastasis of nasopharynx cancer can be observed more often in these areas 36, 37.…”
Section: Discussionmentioning
confidence: 99%
“…The women who did not receive follow‐up were not permanent residents (confirmed by the head of the district), and their new address was not known. An Indonesian‐based study of nasopharyngeal cancer where patients also had low treatment uptake post‐diagnosis, reported that identified barriers included cost of treatment and fear of treatment toxicity, causing them to refrain from treatment or to seek alternative options …”
Section: Discussionmentioning
confidence: 99%
“…An Indonesianbased study of nasopharyngeal cancer where patients also had low treatment uptake post-diagnosis, reported that identified barriers included cost of treatment and fear of treatment toxicity, causing them to refrain from treatment or to seek alternative options. 23 Identification of barriers to seeking treatment, which may include cultural and logistical issues specific to Indonesia, and instigating healthcare systems such as patient navigators for locating patients after an initial positive screening test or diagnosis of breast cancer, are critical. Finally, we report that there is no overall cost saving comparing CBE vs. mammography, in terms of further diagnostic procedures required to identify breast cancers, in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Although NPC is sensitive to radiotherapy and chemotherapy, recurrence rate of NPC during the first 2-year post treatment remains high (2-year progression free survival is less than 53% with median time to progression is 17.4 month) in our centre (Taroeno-Hariadi et al, 2005 unpublished observation). Wildeman et al (2013) reported that median overall survival of NPC patients in our centre is 21 months (95% CI = 18 to 35) from day of diagnosis. Treatment modality, tumor stage, patient performance status, viral load and viral reactivation may influence recurrence and progression (Farias et al, 2003;Twu et al, 2007;Sham and Choy, 2010;Wu et al, 2012).…”
Section: Nasopharyngeal Cancer (Npc) Is a Common Cancer Inmentioning
confidence: 92%